A 5,000-fold increase in the HAT reactivity of a nonheme Fe IV =O complex simply by replacing two pyridines of the pentadentate N4Py ligand with pyrazoles - Nabhendu Pal; Jin Xiong; Mehmet Jahja; Sami Mahri; Victor G. Young; Yisong Guo; Marcel Swart; Lawrence Que (Proceedings of the National Academy of Sciences, 2025)
A pentadentate [N5] ligand (N2Py2Pz) based on the classic N4Py ( N,N -bis(2-pyridylmethyl)- N -bis(2-pyridyl)methylamine) framework has been synthesized by replacing the two pyridylmethyl arms with corresponding ( N -methyl)pyrazolylmethyl units to form [ N- bis(1-methyl-2-pyrazolyl)methyl- N -( bis -2-pyridylmethyl)amine] (L1). The oxidation of the iron(II) precursor (N2Py2Pz)Fe II (OTf) 2 ( 1 ) with ( t BuSO 2 )C 6 H 4 IO at 298 K leads to the formation of the [Fe IV (O)(N2Py2Pz)] 2+ intermediate ( 2 ) with a near-IR band at 750 nm (ε M = 250 M −1 cm −1 ) and a t 1/2 ~ 2 min at 298 K. The introduction of the less basic pyrazolylmethyl ligands in place of two pyridylmethyl units generates Fe IV =O intermediate 2 that exhibits a cyclohexane oxidation rate of 0.29 s −1 at 298 K, which is 5,000-fold faster than that observed for the classic Fe IV (O)N4Py parent complex and 40,000-fold more reactive than the least reactive Fe IV (O)N2Py2Q′ complex in this series (Py = pyridine, Q′ = isoquinoline) recently reported by Nordlander.